Does institutional openness improve the trade efficiency of China’s agricultural products imported from Central Asian countries? A time-varying stochastic frontier gravity model - Cao, Fangfang; Li, Xiande; Zhang, Zhexi (Frontiers in Sustainable Food Systems, 2025)
IntroductionInstitutional openness is becoming increasingly important for agricultural trade between China and Central Asian countries.MethodsThis study employs a time-varying stochastic frontier gravity model to investigate the influence of institutional openness on the trade efficiency of China imported agricultural products from Central Asian countries under uncertainty, and further computes the import potential from 2000 to 2022.ResultsThe research reveals that the impacts of different aspects of institutional openness on trade efficiency vary. Firstly, in terms of border opening measures, the joint accession to the WTO and the signing and implementation of the “Belt and Road Initiative” have effectively enhanced China’s import trade of agricultural products from Central Asian countries. Secondly, regarding the impact of infrastructure, a higher efficiency of trade logistics clearance and a lower tariff are more beneficial for improving the trade efficiency. Thirdly, as for the degree of openness of the socio-economic system, a higher level of economic freedom in Central Asian countries societies are more conducive to promoting the export of agricultural products to China. Additionally, a higher uncertainty of China’s economic policies may enhance the trade efficiency. However, the outbreak of the COVID19 and the Russia-Ukraine war have significantly diminished the trade efficiency. Fourthly, from 2015 to 2022, China’s average export trade efficiency to Central Asian countries range from 0.3 to 0.6, with an import potential value of approximately 2.1 to 2.2 billion US dollars, indicating substantial import potential, especially for Kazakhstan and Uzbekistan.DiscussionIt is recommended to implement the “Belt and Road Initiative”, enhance the logistics infrastructure, improve the efficiency of trade clearance, reduce the tariff burden on agricultural products, and stabilize the trade expectations of Central Asian countries under the unstable external economic environment, thereby enhancing the efficiency of agricultural trade between China and Central Asia countries.